Efficacy of vitamin C supplementation during pregnancy in the prevention of preterm birth: a systematic review and meta-analysis - Alves Pereira, Ana Gabriela [UNESP]; Gonçalves Molino, Gabriela Oliveira; Felix de Farias Santos, Ana Clara; Ferreira Dias, Maírla Marina; Pimenta, Nicole Dos Santos; Costa Matos da Silva, Pedro Henrique (Federação das Associações de Ginecologia e Obstetrícia, 2025)
Objective: Preterm birth is a leading global cause of neonatal mortality and morbidity, with oxidative stress playing a role in its pathogenesis. Vitamin C, a powerful antioxidant, may help reduce this risk. This study assessed the effectiveness of vitamin C supplementation, both alone and with vitamin E, in preventing preterm birth compared to a placebo. Data source: Databases were systematically searched in PubMed, Cochrane and Embase in December 2023 and updated in May 2024. Study Selection: Included RCTs evaluated vitamin C’s effect on preterm birth and related neonatal outcomes. Data collect: Statistical analyses used a random-effects model for pooled risk ratios (RR) and 95% confidence intervals (CI). Heterogeneity was assessed with the I² statistic. Data synthesis: Seventeen RCTs (21,567 patients) were analyzed. Vitamin C supplementation showed no significant difference compared to placebo for preterm birth (RR 1.04; 95% CI 0.96, 1.14). No significant differences were observed for neonatal death (RR 0.77; 95% CI 0.55, 1.08), NICU admission (RR 1.03; 95% CI 0.95, 1.13), preterm PROM (RR 1.04; 95% CI 0.63, 1.71), or birth weight (MD 52.41; 95% CI-19.65, 124.47). A slight decrease in gestational age was observed (MD 0.26; 95% CI-0.02, 0.55). Conclusion: Vitamin C supplementation alone or in combination with vitamin E does not significantly prevent preterm birth or improve related neonatal outcomes.
Keywords: Ascorbic acid; Fetal membranes, premature rupture; Gestational age; Intensive care units, neonatal; Pregnancy; Premature birth; Vitamin C supplementation; Vitamin E